Etude de la toxicité des extraits de certaines plantes sur le stade larvaire L4 de moustique Culex pipiens - Réhab Bekhouche; Hadjer Benallouche (My University, 2022)
The substances of natural origin and more particularly the essential oils of the plants represent currently an alternative solution of fight against mosquitoes. This study aims to test the effect of the essential oils of Cinnamomum camphora, Allium sativum and Urtica dioica to different concentrations on the L4 larvas of Culex pipiens in the conditions of the laboratory and according to the recommendations of the world organization of health (WHO). The results show a variable sensitivity of the larvas; this sensitivity is even more elevated with the increase of the oil concentration. Otherwise, the toxicity is marked well when the length of exhibition of the larvas is longer. The comparison between the: • Three oils (the Cinnamomum camphora, the Allium sativum and the Urtica dioica L) watch that the oil of Cinnamomum camphora is the most efficient. • Three oils and the mixture of two oils (the Cinnamomum camphora + Urtica dioica L), watch that the oil of Cinnamomum camphora is the most efficient • The Three oils and the mixture of the Three oils (the Cinnamomum camphora+ the Allium sativum+ the Urtica dioica L), watch that the mixture is the most efficient The toxicological tests done, revealed the activity larvicide of these Oils. Also the mixture of the three oils is more efficient in relation to the other oils ---------------------------------------------------------------------------------------------------------------------------------------------------- تمثـــــل المـــــواد الطبيعية ذات االصل النباتي بصفـــــة عامـــة وبصفة خاصة الزيوت االساسيــــة للنبات حال بديال لمكافحة البعوض يهـــــدف هذا العمل إلى تقديــــر نسب التأثير السمي بعد المعاملة ليــرقات الطور الرابع لبعوض pipiens Culex بتـراكيز مختلفــة من زيت الكافور، القراص و وتوصيات المنظمة العالمية للصحة )OMS( النتائج بينت وجود حساسية كبيرة لليرقات المعاملة مع زيادة التركيز ، كذلك السمية تزداد كلما كانت مدة المعاملة أطول الثوم ، وهذا تحت الظروف المخبريةكذلك المقارنة بين: • الزيوت الثالث الكافور ، القراص والثوم بينت ان زيت الكافور هو الفعال • الزيوت الثالث و المزيج المكون من ( الكافور و القراص ) بينت كذلك ان الكافور هو الفعال • الزيوت الثالث والمزيج المكون من ( الكافور ، القراص و الثوم ) بينت ان المزيج هو الفعال اختبارات السمية التي أجريت بينت ان هذه الزيوت تملك خصائص مبيد حشري ، وأن المزيج المكون من الزيوت الثالث هو األكثر فعالية مقارنة ببقية الزيوت ----------------------------------------------------------------------------------------------------------------------------------------------------- Les substances d’origine naturelles et plus particulièrement les huiles essentielles des plantes représentent actuellement une solution alternative de lutte contre les moustiques. Cette étude vise à tester l’effet des huiles essentielles d’’Cinnamomum camphora, d’Allium sativum, et d’Urtica dioica L à différentes concentrations sur les larves L4 nouvellement exuviées de Culex pipiens dans les conditions du laboratoire et selon les recommandations de l’organisation mondiale de la santé (OMS). Les résultats montrent une sensibilité variable des larves; cette sensibilité est encore plus élevée avec l'augmentation de la concentration d’huile. Par ailleurs, la toxicité est bien marquée lorsque la durée d'exposition des larves est plus longue. La comparaison entre les : • 3 huiles (l’Cinnamomum camphora, l’Allium sativum et l’Urtica dioica L) montre que l’huile d’Cinnamomum camphora est la plus efficace. • 3 huiles et le mélange de deux huiles (l’Cinnamomum camphora+ Urtica dioica L), montre que l’huile d’Cinnamomum camphora est la plus efficace • Les 3 huiles et le mélange des trois huiles (l’Cinnamomum camphora+ l’Allium sativum+ l’Urtica dioica L), montre que le mélange est la plus efficace. Les tests toxicologiques effectués, ont révélé l’activité larvicide de ces Huiles. De plus le mélange des trois huiles est plus efficace par rapport aux autres huiles